Growth Traits of Anatolian and Anatolian x Italian Crossbred Buffalo Calves Under the Village Conditions - Sekerden, Özel (Journal of Buffalo Science, 2014)
The study was carried out to compare growth performances of Anatolian and crossbred (Anatolian x Italian) buffalo calves (53 F1, 66 Anatolian, 26 F1xAnatolian) raised at Ilıkpınar Village of Kırıkhan District of Hatay Province. Body measurements were determined in the period of 0-12 months of age. The effects of genotype, sex, birth year effects on each characteristic in each age were investigated using GLM variance analysis. The means of each characteristic in each age for each genotype were calculated. Duncan test was used in comparison of the averages of each characteristic SPSS program was used in the statistical procedures. Genotype created significant variation in live weight at 1 and 6 months of ages respectively and on almost every body measurement almost in every age. Genotype* birth weight, genotype*sex, and genotype*birth year* sex interactions were found statistically significant in the point of view of various characteristics in various ages. Factors had significant effects on various characteristics in various ages. It can be said that, F1 growth was the most speedly and Anatolian buffaloes stayed behind of the other genotypes from the point of view of all the traits.